2005
DOI: 10.1590/s1135-57272005000400004
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de los modelos SCORE y Framinghan en el cálculo de alto riesgo cardiovascular para una muestra de varones de 45 y 65 años de Asturias

Abstract: RESUMENFundamento: Recientemente el Comité Español Interdisciplinario para la Prevención Cardiovascular (CEIP) elaboró un consenso para adaptar las recomendaciones de la Guía Europea de Prevención cardiovascular a la población española, utilizando el SCORE como método de cálculo de riesgo. El objetivo de este trabajo es conocer las diferencias que supone pasar del criterio de Framingham al de SCORE en la clasificación de los varones en el grupo de alto riesgo. Métodos:Estudio descriptivo transversal realizado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
3
0
0
Order By: Relevance
“…However, it is highly probable that this contributed to the results seen in the intermediate CVDR category (54 for SCORE vs. 21 for Wilson–Grundy). This study, in accordance with similar studies (10, 11, 14–16), indicates that the SCORE system overestimates CVDR in older male patients than using models based on the Framingham equation. This raises concerns about its use for estimating the cardiovascular risk of the Spanish population (1, 3, 8).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it is highly probable that this contributed to the results seen in the intermediate CVDR category (54 for SCORE vs. 21 for Wilson–Grundy). This study, in accordance with similar studies (10, 11, 14–16), indicates that the SCORE system overestimates CVDR in older male patients than using models based on the Framingham equation. This raises concerns about its use for estimating the cardiovascular risk of the Spanish population (1, 3, 8).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also shown that the SCORE system in patients aged 65–74 years generates a risk double those obtained with methods based on the Framingham equation (15). This same difference is observed in males when the age limit of comparison is drawn at 60 years (16).…”
Section: Discussionsupporting
confidence: 70%
“…We agree with Mostaza et al [11] on the fact that there may be a need to redefine the 5% cut point established for the SCORE model for the Spanish population, according to cardiovascular mortality rates. Our outcomes justify the individualized evaluation of other factors, regardless of risk estimation [12].…”
Section: Discussionsupporting
confidence: 91%
“…Ruiz-Villaverde (30) informa en este misma línea (28,29), que al estimar riesgo cardiovascular en pacientes mayores de 55 años, hipertensos con otros factores de riesgo asociados, con las tablas de SCORE observaba riesgo absoluto y proyectado muy altos, mientras que con las de Framingham, calibradas para población española (31), los mismos pacientes eran estimados de riesgo moderado. Por el contrario, otros autores (32) refieren mayor proporción de alto riesgo a 10 años con Framingham que con SCORE, en un 95% de varones de 60 años con cifras elevadas de colesterol.…”
Section: Se Considera Riesgo Cardiovascularunclassified